Las estrategias metodológicas que utilizan las docentes en el aula y su influencia en el desarrollo cognitivo de los niños y niñas del primer grado de educación básica, paralelo a y b, de la escuela fiscomisional “Cacha”, del cantón El Pangui de la provincia Zamora Chinchipe, periodo 2013-2014.” Lineamientos propositivos - Flores Paladines, Lidia Jhanet (2014)
This thesis refers to " METHODOLOGICAL STRATEGIES USING THE TEACHERS IN THE CLASSROOM AND ITS INFLUENCE ON COGNITIVE DEVELOPMENT OF CHILDREN OF FIRST DEGREE OF BASIC EDUCATION , AND B SIDE , SCHOOL OF FISCOMISIONAL " CACHA " CANTON THE PROVINCE PANGUÍ CHINCHIPE ZAMORA , PERIOD 2013-2014 . " propositional GUIDELINES . The general objective was: To determine the influence of Methodological Strategies in Cognitive Development of Children First Grade Basic Education, Parallel A and B of the Fiscomisional "Cacha” school, The Pangui Canton of the Province of Zamora Chinchipe, 2013-2014. The methods used for the preparation of this research work were: Scientist, Inductive, Deductive, Synthetic, Descriptive and Statistical Model; the techniques used were: Survey applied to the teachers to identify the Methodological strategies they use in daily work and pre- diagnostic test is applied to the children who will assess some important aspects for school learning: verbal, numerical, memory, visual perception and motor coordination. In the implementation of the survey of teachers concluded that: teachers claim that the methodological strategies used by the source of knowledge acquisition are: 100% for work with the textbook and the Oral and Methods 50% for Practical Method. and also The teachers state that the methodological strategies used by the ratio of the activity of student teaching are: 100% independent exhibitions and work . From the results of pre-test diagnosis concludes that children acquired the following results: 82% Positive answers and reached 18% got Negative responses by 100% for work with the textbook and the Oral methods and 50% for Practical Method, and also the teachers state that the Methodological Strategies used by the ratio of the activity of student teaching are: 100% independent exhibitions and work.